Everything - Acuña Torres, Lina Daniela (Universidad Pedagógica y Tecnológica de Colombia, 2021)
A poem written by Lina Daniela Acuña Torres, which talks about an impossible love. She speaks about crying and nights of agony when one is not understood, the incomprehension of those feelings, and the constant search to find someone who understands.